Cyto-IL-15 synergizes with the STING agonist ADU-S100 to eliminate prostate tumors and confer durable immunity in mouse models - Papaevangelou, Efthymia; Esteves, Ana M.; Dasgupta, Prokar; Galustian, Christine (Frontiers in Immunology, 2023)
Introduction Prostate cancer is one of the most commonly diagnosed malignancies in men with high mortality rates. Despite the recent therapeutic advances, such as immunotherapies, survival of patients with advance disease remains significantly low. Blockade of immune checkpoints has led to low response rates in these patients probably due to the immunosuppressive microenvironment and low mutation burden of prostate tumors. Combination of multiple immunotherapeutic regimes has also been unsatisfactory due to augmented adverse effects. To activate multiple immune-stimulatory pathways in the hostile prostate cancer microenvironment, we used a combination of cytotopically modified interleukin-15 (cyto-IL-15) with the stimulator of interferon genes (STING) agonist, ADU-S100. Methods To determine whether this combination regime could lead to both local and systemic anti-tumor effects, intratumoral administration of these agents was used in murine models of prostate cancer. Tumor growth and mouse survival were monitored, and ex vivo analyses, and RNA sequencing were performed on the tumors. Results Intratumorally injected ADU-S100 and cyto-IL-15 synergized to eliminate tumors in 58-67% of mice with unilateral tumors and promoted abscopal immunity in 50% of mice with bilateral tumors treated only at one side. Moreover, this combination regime offered immunoprotection against tumor rechallenge in 83% of cured mice. The efficacy of the combination treatment was associated with a strong innate and adaptive immune activation and induction of apoptotic and necrotic cell death. Cytokines, including type I and II interferons, and cytokine signalling pathways were activated, NK and T cell mediated cytotoxicity was increased, and B cells were activated both locally and systemically. While ADU-S100 led to an ulcerative pathology at the injection site, no other adverse effects were observed. Discussion Localised administration of a STING agonist together with cyto-IL-15 can confer significant systemic benefits and long-lasting immunity against prostate tumors while reducing immune related toxicities.